Peningkatan Kemampuan Kognitif melalui Kegiatan Bermain Palydough bagi Anak Usia 5-6 Tahun - Ngawan, Elfrida Suriani; Cahaya, I Made Elia; Prima, Elizabeth (Universitas Negeri Malang, 2024)
One of the abilities that must be developed in children is cognitive abilities. Cognitive ability is a thinking process in the form of the ability or power to connect an event with another event as well as the ability to assess and consider everything that is observed from the world around. Cognitive abilities can be stimulated through playing while learning. One of them can be done by playing Playdough. This study aims to determine the increase in cognitive abilities of early childhood through playing Playdough in Group B2 TK Widya Kumara Tangeb children. This research is a classroom action research carried out in 2 cycles with the stages of planning, action, observation, and reflection in each cycle. The subjects of this study were the children of Group B2 Kindergarten Widya Kumara Tangeb for the 2022/2023 Academic Year, totaling 24 children. The object of this research is to improve cognitive abilities through playing Playdough. Data collection methods are documentation, observation, and interviews. The analysis technique used in this research is quantitative descriptive analysis. The results of this study indicate that the criteria for the completeness of the cognitive abilities of the children in Group B2 Kindergarten Widya Kumara Tangeb at the initial observation were 20.83%, in Cycle I was 45.83%, and in Cycle II was 87.50%. Thus the application of playing Playdough can improve the cognitive abilities of Group B2 TK Widya Kumara Tangeb children